Down Under. - Benijts, Frank; Matthys, Danny; Ebes, Henk; Museum Dhondt Dhaenens Deurle; Aboriginal Gallery of Dreamings, Melbourne ([S.l.] : [s.n.], 1993)
Jangala Jumbyinmba, Abi ; Tjampatjinpa, Anatjari ; Stockman Tjapaltjarri, Billy ; Egalie Tjapaltjarri, Charlie ; Possum Tjapaltjarri, Clifford ; Matthys, Danny ; Martin, Dominic ; Kame Kngwarreye, Emily ; Possum Nungurrayi, Gabriella ; Bush Tjangala, George ; Kenmarre, Gladys ; Britten Joolama, Jack ; Forrester Nangala, Janet ; Skinner, Johnny ; Tjampitjinpa, Kaapa ; Kuddtji ; Napangardi Watson, (Old) Maggie ; Jagamarra Maloney, Malcolm ; Tjampitjinpa, Maxi ; Jaminji Jampin, Paddy ; Napangati, Pansy ; Nuputtula, Polly ; Tax Tjupurrula, Richard ; Thomas, Rover ; Tolson Tjupurrula, Turkey ; Tjangala, Uta Uta
DOWN UNDER, Museum Dhondt-Dhanens, Deurle, 07.11. - 12.12.1993
boek